Digitaliserede økonomier har klaret sig bedre gennem pandemien - Amy Yuan Zhuang (Danmarks Nationalbank, 2021)
– The pandemic has accelerated the digital transition in many countries. This Economic Memo finds that the degree of digitalisation has had an impact on the magnitude of economic losses during the pandemic. Differences in the EU countries' objectives for digital transition can imply greater digital inequality in the future and a deeper economic gap between the countries.
Keywords: 330; Digitalisierung; Coronavirus; Dänemark; EU-Staaten